2015
DOI: 10.1016/j.pharep.2015.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Berberine and neurodegeneration: A review of literature

Abstract: The excessive production of reactive oxygen species in nervous tissues is considered one of the major risk factors of neurodegenerative diseases. During the last two decades, much attention has been paid to the antioxidant and anti-inflammatory activity of natural products and compounds isolated from natural products which are often characterized by high efficacy and low adverse effects. Berberine is an isoquinoline alkaloid, widely present in different medicinal herbs, especially in the genus Berberis. It is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
68
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(81 citation statements)
references
References 162 publications
2
68
0
2
Order By: Relevance
“…Berberine has also been reported to show efficacy in HD models, and is postulated to induce autophagy via AMPK activation 110,111 . Many other molecules including clonidine 112 , modulate cyclic AMP or inositol triphosphate to induce autophagy and ameliorate phenotypes in HD animal models.…”
Section: Therapeutic Approaches In Hd Targeting Autophagymentioning
confidence: 99%
“…Berberine has also been reported to show efficacy in HD models, and is postulated to induce autophagy via AMPK activation 110,111 . Many other molecules including clonidine 112 , modulate cyclic AMP or inositol triphosphate to induce autophagy and ameliorate phenotypes in HD animal models.…”
Section: Therapeutic Approaches In Hd Targeting Autophagymentioning
confidence: 99%
“…Currently, there is an increasing interest in berberine due to its favorable biological activities, and there have been many studies regarding its pharmacokinetic properties [2][3][4] and pharmacological activities [5]. In clinical practice and some trials, berberine has been shown to have therapeutic effects on several clinical disorders, including neurodegenerative diseases [6][7][8], cancer [9], cardiological problems [10,11], metabolic syndrome [12], mood disorders [13], and hepatic and renal disorders [14], indicating that berberine has potential for further development as a natural drug.…”
Section: Introductionmentioning
confidence: 99%
“…It can significantly regulate blood sugar levels and improve impaired glucose tolerance. In addition, it has preferable preventive and therapeutic effects against diabetic complications, such as cardiovascular disease, hypertension and hyperlipidemia (8). As an isoquinoline derivative alkaloid, berberine exists in Coptischinensis, golden cypress and the root of Chinese barberry (8).…”
Section: Introductionmentioning
confidence: 99%